Integration of Computer-Based Learning Media and Problem-Based Learning Models to Develop Critical Thinking Abilities in Early Childhood - Widyawati, Widyawati; Eka Saputra, Erwin (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to examine the effect of integrating computer-based learning media with the Problem-Based Learning (PBL) model on the development of critical thinking skills in early childhood education. Specifically, the study focuses on how this integration enhances children’s abilities to analyze, interpret, infer, and evaluate information, as well as its impact on motivation, creativity, independence, and learning engagement. Research Method: This study employed a quantitative approach with a quasi-experimental design using a Pretest–Posttest Control Group Design. The sample consisted of 30 children in Group B at TK Pertiwi No. 3 Pattiro Bajo, Bone Regency, who were randomly assigned to an experimental group and a control group. The experimental group received instruction using computer-based learning media integrated with the PBL model, while the control group received conventional instruction. Data were collected through observation sheets measuring children’s critical thinking skills and were analyzed using normality tests, homogeneity tests, and independent samples t-tests. Research Findings: The results indicate that the experimental group showed a statistically significant improvement in critical thinking skills compared to the control group. The mean posttest score of the experimental group increased from 65.3 to 83.1, while the control group only increased from 64.9 to 71.5. The t-test results revealed a significant difference between the two groups (p < 0.05), confirming that the integration of computer-based learning media with the PBL model effectively enhances early childhood learners’ critical thinking abilities, including analysis, reasoning, and conclusion-drawing skills. Novelty: This study demonstrates that the integration of computer-based learning media with the PBL model is an innovative and effective pedagogical strategy for early childhood education. The novelty lies in applying a synergistic digital–problem-based approach at the early childhood level, which not only improves critical thinking skills but also strengthens motivation, creativity, independence, and sustained engagement. The findings contribute new insights into how technology-supported PBL can be used to foster higher-order thinking skills from an early age.